The use of high-speed internet as a platform for compulsive online buying: a case of study of post-graduate students in Malaysia - Adhwa Hasmin Hussain; Abdul Manaf Bohari (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Online compulsive buying is chronic buying phenomena in which the consumer feels unable to stop or significantly moderate the behavior of buying. In other words, it is an addiction of buying things through the Internet .This study investigates differences in demographic factors that could explain the profile of online compulsive buyers, and examines the influence of high speed Internet connection on compulsive online buying behavior. A hundred respondents of post-graduate students at Universiti Utara Malaysia were selected to participate in the study. Questionnaires were distributed randomly to obtain the data. The findings showed that all demographic factors examined are insignificant in differentiating the profile of compulsive online buyers. Also, the study found that the high-speed Internet connection did not significantly influence compulsive online buying behavior. Nevertheless, it was recommended that marketers introduce cash card as an alternative mode of payment apart from the credit card as the many Malaysians still do not possess credit cards. For future research endeavors, larger sample sizes and more diversified aspects of compulsive online buying would certainly improve results.